Analysis of Hypocenter Position of Bengkulu Earthquake on April 15, 2023 Using 2D and 3D Grid Search Method Based on USGS Data - Firdos Bahar Sidik; Savira Zahrul Khumairo; Farizki Budi Pangestu; Triya Illmi Sakinah; Muhamad Raihan Putra Febrian; Risaldi Fauzan Laksono; Jihan Syafina Nasution (Lambung Mangkurat University Press, 2024)
Earthquakes are natural events that can have serious impacts on human life and the environment. This study aims to improve the accuracy of earthquake hypocenter determination by applying the 2D dan 3D Grid Search method to seismic data recorded by three stations in the Bengkulu area, Indonesia. The analysis process begins with P and S wave phase picking using seismograv software, followed by origin time determination using the Wadati diagram method. The 2D dan 3D Grid Search method was used to calculate the position of the earthquake hypocenter by dividing the search area into grids and searching for the smallest RMS value. The results of the relocation calculation obtained the hypocenter point of the earthquake at latitude 4.50°N, longitude 76.0340°W with a depth of 60 km. Although there are differences with USGS data, the level of agreement of the calculation results is relatively high. This research contributes to further understanding of earthquakes in the study area and can be the basis for improving disaster mitigation.